Application of XPS imaging analysis in understanding interfacial delamination and X‐ray radiation degradation of PMMA. (8th August 2013) - Piao, Hong; Fairley, Neal; Walton, John
<x xml:space="preserve">Abstract</x> The recent development of X‐ray Photoelectron Spectroscopy (XPS) instrumentation with spatial resolution down to several microns has advanced the capability of elemental and chemical state imaging. XPS imaging analysis has been applied in understanding the delamination problems of siloxane coatings on polymethyl‐methacrylate (PMMA) polymer. It was found that delamination occurred by interfacial failure, and the coating suffered complete delamination from a PMMA substrate. This example offered an opportunity for the investigation of X‐ray damage on polymers encountered in XPS imaging analysis. This paper also demonstrated how to construct a constrained peak model with the aid of chemical knowledge and supporting evidence of the sample. Monte Carlo error analysis was used to determine the validity of the peak fit models used. Copyright © 2013 John Wiley & Sons, Ltd.